Silicone resin composition, cured product of silicone resin composition, and optical semiconductor device

JP2025019645APending Publication Date: 2025-02-07SHIN ETSU CHEMICAL CO LTD
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
JP2023123364
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07
Patent Text Reader

Abstract

To provide an addition reaction-curable silicone resin cured product that increases a glass transition temperature Tg and offers high resistance to gas permeation.SOLUTION: A silicone resin composition comprises: (A) a branched-chain organopolysiloxane, represented by the following average formula, with aryl groups bound to silicon atoms making up 10% or more of the total number of substituents bound to silicon atoms, and with at least two silicon-bonded alkenyl groups being present in each molecule, (SiO4 / 2)a(R1SiO3 / 2)b(R2SiO3 / 2)c(R2R3SiO2 / 2)d, (B) a hydrosilyl group-containing organic silicon compound with two or more SiH groups in one molecule, in such an amount that the ratio of the number of hydrosilyl groups in component (B) to the number of alkenyl groups in component (A) is 0.1 to 4.0; and (C) a platinum group metal-based catalyst in a catalytic amount.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silicone resin composition that gives a cured product having high gas permeability resistance, and to an optical semiconductor device having the cured product. [Background technology]

[0002] Organopolysiloxanes have excellent heat resistance, cold resistance, electrical insulation, light resistance, weather resistance, light transparency, gas permeability, and chemical stability, and are used as excellent materials in a wide variety of fields, from the electrical and electronic fields to transportation equipment, office supplies, cosmetics, and the medical field. Among them, addition-curable silicone resin compositions (hereinafter referred to as silicone resin compositions), which have excellent transparency, are used as materials for optical semiconductors such as LEDs.

[0003] In recent years, optical semiconductor devices have been used as LED lighting for outdoor lighting or vehicle lighting. Resins with high gas or moisture permeability, such as silicone resins, are generally used as encapsulants for such optical semiconductor devices. Therefore, in harsh environments such as outdoors, there is a problem that the silver plating layer used as the electrode or reflective layer of the optical semiconductor device is corroded by sulfur-based gas or moisture, resulting in a significant decrease in brightness.

[0004] As a countermeasure, the introduction of aromatic substituents such as phenyl groups to increase the refractive index and improve gas permeability resistance has been investigated (Patent Document 1), but there is a limit to the proportion of phenyl groups that can be contained in one silicone molecule due to steric hindrance, etc. In addition, when phenyl silicone is normally used, the glass transition temperature Tg is about 50°C, and there is a sudden decrease in the elastic modulus around that temperature, which causes a significant decrease in gas permeability resistance in the medium to high temperature range, which is also a problem.

[0005] In addition, known corrosion inhibitors for preventing metal corrosion include compounds of N-containing aromatic hydrocarbons such as benzotriazole and 5-methylbenzimidazole, and metal complexes such as zinc, and attempts to add these corrosion inhibitors are being considered. However, there is a problem that the heat resistance of the resin is greatly reduced due to discoloration of the corrosion inhibitor and metal ligands (Patent Document 2).

[0006] Furthermore, resin compositions using polyorganosiloxanes containing a thiazole compound or triazine compound in the siloxane skeleton have also been developed. However, depending on the curing method of the silicone resin composition, there is a risk that the curing may be inhibited, and in addition-curing type resin compositions, they act on platinum and the like, becoming a catalyst poison, making them difficult to use (Patent Document 3). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-185293 A [Patent Document 2] JP 2012-056251 A [Patent Document 3] JP 2012-251058 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made in view of the above problems, and has an object to provide an addition reaction curable silicone resin cured product that has an increased glass transition temperature Tg and excellent gas permeability resistance. [Means for solving the problem]

[0009] As a result of intensive research aimed at solving the above problems, the present inventors have discovered an RSiO having an alkenyl group and an aryl group. 3 / 2 Units (T units) and / or R 2 SiO 2 / 2The present inventors have discovered that an addition reaction curable silicone resin composition containing a branched organopolysiloxane having a specific ratio of units (D units) can increase the glass transition temperature Tg of the cured product and provide a silicone resin cured product with excellent gas permeation resistance, which has led to the completion of the present invention.

[0010] That is, the present invention provides (A) A branched-chain organopolysiloxane represented by the following average formula, which has 10% or more aryl groups bonded to silicon atoms relative to the total number of substituents bonded to silicon atoms and has at least two silicon-bonded alkenyl groups per molecule: (SiO 4 / 2 ) a (R 1 SiO 3 / 2 ) b (R 2 SiO 3 / 2 ) c (R 2 R 3 SiO 2 / 2 ) d (1) (In the above formula, R 1 are each independently a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyl group other than an alkenyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms; R 2 are each independently an alkenyl group having 2 to 10 carbon atoms; R 3 are each independently a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyl group other than an alkenyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms, and a, b, c, and d are numbers that satisfy a ≧ 0, b > 0, c ≧ 0, and d ≧ 0, with the proviso that c + d > 0 and a + b + c + d = 1. (B) a hydrosilyl group-containing organosilicon compound having two or more SiH groups per molecule, in an amount such that the ratio of the number of hydrosilyl groups in component (B) to the number of alkenyl groups in component (A) is 0.1 to 4.0, and (C) Platinum group metal catalyst catalyst amount The present invention provides a silicone resin composition comprising:

[0011] The silicone resin composition of the present invention further comprises at least one of the components listed in [1] to [3] below. [1] The silicone resin composition, wherein in the above formula (1), a is a number from 0 to 0.6, b is a number from 0.1 to 0.9, c is a number from 0 to 0.5, and d is a number from 0 to 0.5, and c+d>0 and a+b+c+d=1 is satisfied. [2] The silicone resin composition, wherein the component (B) is an organosilicon compound selected from organohydrogen(poly)siloxanes, organo(poly)silphenylenes, and organo(poly)silphenylenesiloxanes, having 2 to 200 silicon atoms per molecule and having one or more silicon-bonded aryl groups per molecule. [3] The silicone resin composition as described above, wherein the component (A) has a weight average molecular weight of 1,000 to 50,000 as determined by gel permeation chromatography (GPC) using polystyrene as a standard substance.

[0012] The present invention also provides a cured product of the above silicone resin composition, which further comprises at least one of the components shown in [1] and [2] below. [1] The cured product, characterized in that the type D hardness of the cured product, measured by the method described in JIS K 6253-3, is in the range of 30 to 90. [2] The cured product as described above, characterized in that the refractive index at a wavelength of 589 nm, measured by the method specified in JIS K 0062, is in the range of 1.45 to 1.60. The present invention further provides an optical semiconductor device comprising the cured product and an optical semiconductor element.

[0013] The cured product obtained by curing the silicone resin composition of the present invention preferably has a type D hardness measured by the method described in JIS K 6253-3 in the range of 30 to 90. A cured product having such a hardness has excellent resin strength and can be highly reliable.

[0014] The cured product obtained by curing the silicone resin composition of the present invention preferably has a refractive index in the range of 1.45 to 1.60 at a wavelength of 589 nm, as measured by the method described in JIS K 0062. The silicone resin composition which gives a cured product having such a direct light transmittance can be particularly suitably used for optical applications such as LED encapsulants. Effect of the Invention

[0015] The present invention provides an addition reaction curing type silicone resin composition containing a branched-chain organopolysiloxane having a specific structure, and can provide a cured product having excellent gas permeability resistance and reliability. The silicone resin composition can provide a cured product having excellent mechanical properties, transparency, and sulfurization resistance. The addition reaction curing type silicone resin composition of the present invention is suitable for use as a lens material for a light-emitting semiconductor device, a protective coating agent, a molding agent, etc., and a semiconductor device including a cured product of the composition and a semiconductor element can ensure long-term reliability under high humidity conditions, and can provide a light-emitting semiconductor device having good moisture resistance and long-term color rendering properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below, but the present invention is not limited thereto. [(A) Branched Organopolysiloxane] The silicone resin composition of the present invention is characterized by containing a branched-chain organopolysiloxane of a specific structure, which exhibits high gas permeability resistance and provides a cured product that is stable under high temperature and high humidity conditions. More specifically, component (A) has 10% or more of aryl groups bonded to silicon atoms based on the total number of substituents bonded to silicon atoms. A silicone resin composition containing such a branched-chain organopolysiloxane provides a cured product with excellent gas permeability resistance. More specifically, the component (A) of the present invention is a branched-chain organopolysiloxane represented by the following average composition formula (1). (SiO 4 / 2 ) a (R 1 SiO 3 / 2 ) b (R2 SiO 3 / 2 ) c (R 2 R 3 SiO 2 / 2 ) d (1) (In the above formula, R 1 are each independently a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms other than an alkenyl group, or an aryl group having 6 to 10 carbon atoms; R 2 is an alkenyl group having 2 to 10 carbon atoms, R 3 are independently a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms other than an alkenyl group, or an aryl group having 6 to 10 carbon atoms; and a, b, c, and d are numbers that satisfy a≧0, b>0, c≧0, and d≧0, with the proviso that c+d>0 and a+b+c+d=1.

[0017] The component (A) is characterized in that it contains 10% or more of aryl groups bonded to silicon atoms based on the total number of substituents bonded to silicon atoms. More preferably, it contains 10 to 90% of aryl groups bonded to silicon atoms based on the total number of substituents bonded to silicon atoms. Even more preferably, it is 35% to 90%, and the lower limit is even more preferably 50% or more. By containing the aryl groups at the above lower limit or more, the effect of increasing gas permeability resistance can be obtained. On the other hand, if the above upper limit is exceeded, the aromatic groups will be too numerous, resulting in a rigid structure, and the resulting resin composition may become brittle.

[0018] The above-mentioned component (A) is an organopolysiloxane having a resin structure. The organopolysiloxane is characterized by having a specific ratio of T units and / or D units having alkenyl groups and aryl groups. That is, R 1 SiO 3 / 2 It includes a unit (hereinafter referred to as T unit) as a requirement, and 2 R 3 SiO 2 / 2 Units (hereinafter referred to as D units) and R 2 SiO 3 / 2At least one T unit (hereinafter referred to as T unit) and optionally SiO 4 / 2 In the above average composition formula (1), a, b, c, and d are numbers that satisfy a≧0, b>0, c≧0, and d≧0, respectively, with the proviso that c+d>0 and a+b+c+d=1. 4 / 2 The ratio a of the number of units is preferably 0 to 0.6, and more preferably 0 to 0.5. 1 SiO 3 / 2 The ratio b of the number of units is preferably 0.1 to 0.9, and more preferably 0.3 to 0.8. In addition, it is preferable that a+b is a number of 0.5 or more. R 2 SiO 3 / 2 c indicates the ratio of the number of units, and R when the total number of siloxane units is 1 2 R 3 SiO 2 / 2 Each d, which indicates the ratio of the number of units, is preferably 0 to 0.5, and more preferably 0 to 0.3, independently of each other. c+d is a number exceeding 1, preferably 0.01 to 0.7, and more preferably 0.1 to 0.5. The component (A) of the present invention is preferably R 3 SiO 1 / 2 It does not have any M units (hereinafter referred to as M units, where R is a monovalent hydrocarbon group), and in particular does not have any M units having an alkenyl group.

[0019] In the above, R 1 are each independently a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms; R 2 is an alkenyl group having 2 to 10 carbon atoms, R 3 R independently represents a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, preferably 1 to 5 carbon atoms, a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 1 and R 3More specifically, R includes lower alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclohexyl; aryl groups such as phenyl, tolyl, and xylyl; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl; and groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms such as fluorine, bromine, and chlorine, or with cyano groups, such as chloromethyl, cyanoethyl, and 3,3,3-trifluoropropyl. Of these, methyl and phenyl groups are preferred. As alkoxy groups, methoxy and ethoxy groups are preferred. R 2 Examples of the alkyl group include alkenyl groups such as vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, cyclohexenyl, and octenyl. Of these, vinyl is preferred.

[0020] Component (A) has at least two silicon-bonded alkenyl groups per molecule. The amount of alkenyl groups contained in component (A) is preferably 0.01 to 0.5 mol / 100 g, more preferably 0.05 to 0.3 mol / 100 g, and even more preferably 0.10 to 0.25 mol / 100 g. If the amount of alkenyl groups bonded to silicon atoms is less than 0.01 mol / 100 g, there may be few crosslinks and the composition may not solidify. If it exceeds 0.5 mol / 100 g, the crosslink density may increase and toughness may be lost.

[0021] In component (A), the amount of hydroxyl groups bonded to silicon atoms is preferably 0.001 to 1.0 mol / 100 g, more preferably 0.005 to 0.8 mol / 100 g, and even more preferably 0.008 to 0.6 mol / 100 g.

[0022] In component (A), the amount of alkoxy groups bonded to silicon atoms is preferably 1.0 mol / 100 g or less, more preferably 0.8 mol / 100 g or less, and even more preferably 0.5 mol / 100 g or less. There is no particular lower limit to the amount of alkoxy groups, and the lower the better. If the amount of alkoxy groups exceeds 1.0 mol / 100 g, alcohol gas is generated as a by-product during curing, and voids may remain in the cured product. In the present invention, the amount of hydroxyl groups and the amount of alkoxy groups bonded to silicon atoms are 1 H-NMR and 29 This refers to the value measured by Si-NMR.

[0023] The branched-chain organopolysiloxane preferably has a weight average molecular weight (Mw) of 1,000 to 50,000, more preferably 1,000 to 20,000, and even more preferably 2,000 to 15,000. If the molecular weight is less than the lower limit, the composition may become brittle, and if the molecular weight is more than the upper limit, the composition may become too viscous to flow. The weight average molecular weight (Mw) in the present invention is the weight average molecular weight measured by gel permeation chromatography (GPC) using polystyrene as the standard, and may be measured under the following conditions. [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.6mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) TSKgel SuperH2000(6.0mmI.D.×15cm×2) (Both manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (THF solution with a concentration of 0.5% by mass)

[0024] SiO4 / 2 Examples of materials for obtaining the units (Q units) include, but are not limited to, sodium silicate, tetraalkoxysilane, or condensation products thereof.

[0025] R 1 SiO 3 / 2 Units and R 2 SiO 3 / 2 Examples of materials for obtaining units (T units) include, but are not limited to, organosilicon compounds such as organotrichlorosilane and organotrialkoxysilane represented by the following structural formulas, or condensation products thereof. [ka] (In the above formula, Me represents a methyl group.)

[0026] R 2 R 3 SiO 2 / 2 Examples of materials for obtaining units (D units) include organosilicon compounds such as diorganodichlorosilane and diorganodialkoxysilane represented by the following structural formulas, but are not limited thereto. [ka]

[0027] [(B) Hydrosilyl group-containing organosilicon compound] Component (B) is a hydrosilyl group-containing organosilicon compound that has two or more hydrogen atoms bonded to silicon atoms in one molecule (hereafter referred to as hydrosilyl groups), and reacts with component (A) to act as a crosslinking agent.

[0028] Component (B) is preferably an organosilicon compound having two or more hydrosilyl groups in one molecule, selected from organohydrogen(poly)siloxane, organo(poly)silphenylene, and organo(poly)silphenylenesiloxane. Organosilicon compounds having 2 to 200 silicon atoms in one molecule and having one or more silicon-bonded aryl groups in one molecule are preferred. The organohydrogen(poly)siloxane is, for example, represented by the following average composition formula (2). The organo(poly)silphenylene is, for example, represented by the following average composition formula (3). Alternatively, it may be an organohydrogen(poly)silphenylenesiloxane having in its molecule a siloxane structure represented by the average composition formula (2) and a silphenylene structure represented by the following average composition formula (3). R 4 h H i SiO (4-h-i) / 2 (2) R 4 h H i SiPh (4-h-i) / 2 (3) In the formula, R 4 are each independently an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms or an aryl group having 6 to 10 carbon atoms, and h and i are positive numbers satisfying 0.7≦h≦2.1, 0.001≦i≦1.0 and 0.8≦h+i≦3.0, and preferably 1.0≦h≦2.0, 0.01≦i≦1.0 and 1.5≦h+i≦3.0. In the above formula (3), Ph is a divalent benzene ring (phenylene), and more preferably a p-phenylene group.

[0029] Above R 4 Examples of the alkyl group include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, cyclopentyl, and cyclohexyl groups, aryl groups such as aralkyl groups such as phenyl, tolyl, xylyl, benzyl, phenylethyl, and phenylpropyl groups, and groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups have been substituted with halogen atoms such as fluorine, bromine, and chlorine, halogenated hydrocarbon groups such as trifluoropropyl and chloropropyl groups, and epoxy groups such as allylglycidyl groups. Of these, alkyl groups having 1 to 5 carbon atoms such as methyl, ethyl, and propyl groups, and phenyl groups are preferred.

[0030] Component (B) preferably has one or more silicon-bonded aryl groups per molecule, and more preferably has 1 to 100 silicon-bonded aryl groups per molecule, and more preferably has 1 to 70 silicon-bonded aryl groups per molecule.

[0031] The (B) component preferably has at least 2 and no more than 200 hydrosilyl groups in one molecule. The lower limit is more preferably 3 or more. The upper limit is more preferably 100 or less, and even more preferably 80 or less.

[0032] The molecular structure of component (B) is not particularly limited, and any molecular structure can be used as component (B), such as linear, cyclic, branched, three-dimensional network (resin-like), etc. When component (B) has a linear structure, the hydrosilyl group may be bonded to a silicon atom only at either the molecular chain terminal or the molecular chain side chain, or may be bonded to a silicon atom at both.

[0033] One embodiment of the component (B) is an organohydrogen(poly)siloxane having a number of silicon atoms (or degree of polymerization) in one molecule of 2 to 200, preferably 3 to 100, more preferably 3 to 70, even more preferably 3 to 50, and still more preferably 3 to 30. Organohydrogen(poly)siloxanes that are liquid or solid at room temperature (25° C.) are preferred. Another embodiment of component (B) is a compound having a silphenylene structure and having hydrogen atoms bonded to two or more silicon atoms in one molecule. Preferably, it is an organo(poly)silphenylene having a silphenylene structure and having hydrosilyl groups at both ends of the molecular chain, and the number (or degree of polymerization) of silicon atoms in one molecule is 2 to 50, more preferably 2 to 30, and even more preferably 2. Another embodiment of the component (B) may be an organohydrogen(poly)silphenylenesiloxane having a silphenylene structure, as described above. The number of silicon atoms (or degree of polymerization) in one molecule is usually 2 to 200, preferably 3 to 100, more preferably 3 to 70, even more preferably 3 to 50, and even more preferably 3 to 30, similar to organohydrogen(poly)siloxanes.

[0034] Examples of organohydrogenpolysiloxanes represented by the above average composition formula (2) include tris(hydrogendimethylsiloxy)phenylsilane, copolymers of methylhydrogensiloxane / diphenylsiloxane capped at both ends with trimethylsiloxy groups, copolymers of methylhydrogensiloxane / diphenylsiloxane / dimethylsiloxane capped at both ends with trimethylsiloxy groups, copolymers of methylhydrogensiloxane / methylphenylsiloxane / dimethylsiloxane capped at both ends with trimethylsiloxy groups, copolymers of methylhydrogensiloxane / dimethylsiloxane / diphenylsiloxane capped at both ends with dimethylhydrogensiloxy groups, copolymers of methylhydrogensiloxane / dimethylsiloxane / diphenylsiloxane capped at both ends with dimethylhydrogensiloxy groups, (CH 3 ) 2 HSiO 1 / 2 Units and SiO 4 / 2 Units and (C 6 H 5 ) 3 SiO 1 / 2 and copolymers consisting of units.

[0035] More specifically, component (B) includes hydrosilyl group-containing organosilicon compounds represented by the following structures, but is not limited to these. [ka] [ka] [ka] (p, q, and r are each an integer greater than or equal to 0, and p+q+r is a number between 3 and 500.)

[0036] In the silicone resin composition of the present invention, the amount of component (B) is an amount such that the ratio of the number of hydrosilyl groups in component (B) to the number of alkenyl groups bonded to silicon atoms in component (A) is 0.1 to 4.0, preferably 0.5 to 3.0, more preferably 0.8 to 2.0. If the amount of component (B) is less than the above lower limit, the curing reaction of the silicone resin composition does not proceed, making it difficult to obtain a cured product, and the crosslink density of the obtained cured product becomes too low, resulting in insufficient mechanical strength and poor heat resistance. On the other hand, if the amount of component (B) is more than the above upper limit, a large amount of unreacted hydrosilyl groups remain in the cured product, causing changes in physical properties over time and a decrease in the heat resistance of the cured product, and further causing foaming due to dehydrogenation reaction in the cured product.

[0037] [(C) Platinum group metal catalyst] Component (C) is a catalyst that promotes the hydrosilylation reaction between components (A) and (B). Any conventionally known platinum group metal catalyst can be used as the catalyst. Considering cost and other factors, platinum-based catalysts such as platinum, platinum black, and chloroplatinic acid are preferred. For example, H 2 PtCl 6 pH 2 OK 2 PtCl 6 ,KHPtCl 6 pH 2 OK 2 PtCl 4 ,K 2 PtCl 4 pH 2 O,PtO 2 pH 2 O,PtCl 4 pH 2 O,PtCl 2 ,H 2 PtCl 4 pH 2O (where p is a positive integer), complexes of these with hydrocarbons such as olefins, alcohols, or vinyl group-containing organopolysiloxanes, and photoactive complexes such as trimethyl(methylcyclopentadienyl)platinum, etc. These catalysts can be used alone or in combination of two or more.

[0038] The amount of the catalyst (C) is a catalytic amount and is not particularly limited. It should be an effective amount for promoting the hydrosilylation reaction of the components (A) and (B). Usually, the amount is 0.1 to 500 ppm by mass of platinum group metal relative to the total amount of the components (A) and (B), and more preferably 0.5 to 100 ppm by mass.

[0039] [(D) Solvent] The component (D) is a solvent for improving the fluidity of the resin composition. Any conventionally known organic solvent can be used as the solvent. Examples of the solvent include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene, esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate, ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, cyclopentanone, and methyl isobutyl ketone, ethers such as diethyl ether, diisopropyl ether, methyl-tert-butyl ether, and ethylcyclopentyl methyl ether, and chlorine-based solvents such as methylene chloride, chloroform, dichloroethane, and trichloroethylene. These solvents can be used alone or in combination of two or more. The amount of the solvent may be appropriately adjusted within a range that does not impair the effects of the present invention. The amount of the solvent is preferably 50 parts by mass or less, and more preferably 1 to 30 parts by mass, per 100 parts by mass of the total of the components (A) and (B).

[0040] [Other additives] The silicone resin composition of the present invention may contain, in addition to the above-mentioned components (A), (B), and (C), other additives as appropriate. Examples of other additives include reinforcing inorganic fillers such as silica, glass fiber, and fumed silica, inorganic white pigments such as titanium dioxide, zinc oxide, zirconium oxide, calcium carbonate, magnesium oxide, aluminum hydroxide, barium carbonate, magnesium silicate, zinc sulfate, and barium sulfate, non-reinforcing inorganic fillers such as calcium silicate, carbon black, cerium fatty acid salts, barium fatty acid salts, cerium alkoxides, and barium alkoxides, silver (Ag), aluminum (Al), aluminum nitride (AlN), boron nitride (BN), silicon dioxide (silica: SiO 2 ), aluminum oxide (alumina: Al 2 O 3 ), iron oxide (Fe 2 O 3 ), triiron tetroxide (Fe 3 O 4 ), lead oxide (PbO 2 ), tin oxide (SnO 2 ), cerium oxide (Ce 2 O 3、 CEO 2 ), calcium oxide (CaO), manganese tetroxide (Mn 3 O 4 Examples of fillers include fillers such as barium oxide (BaO). The amount of the additive may be appropriately adjusted within a range that does not impair the effects of the present invention. The amount of the additive is preferably 600 parts by mass or less, and more preferably 10 to 400 parts by mass, per 100 parts by mass of the total of components (A) and (B).

[0041] The silicone resin composition of the present invention can be cured after being applied to a predetermined substrate according to the application. As for the curing conditions, the composition can be sufficiently cured at room temperature (25°C), but may be cured by heating if necessary. When heating, the composition can be cured at a temperature of, for example, 60 to 200°C.

[0042] The hardness of the cured product of the composition of the present invention, measured using a durometer type D hardness tester in accordance with JIS K 6253-3, is 30 to 90, preferably 35 to 85, and more preferably 40 to 80. If the hardness is less than 30, the strength is insufficient, while if it exceeds 90, the strength is excellent but the resin becomes too rigid, which tends to cause deterioration in reliability, such as cracking and peeling of the resin.

[0043] The cured product of the composition of the present invention has a refractive index of 1.45 to 1.60, preferably 1.47 to 1.60, and more preferably 1.50 to 1.60 at a wavelength of 589 nm as measured by the method described in JIS K 0062. If the refractive index is less than 1.45, the antireflection effect is poor, while if it exceeds 1.60, the antireflection effect is excellent but the functions as an optical semiconductor device, such as light transmittance, are poor.

[0044] The silicone resin composition of the present invention can be used for various applications such as, but not limited to, sealing materials, adhesives, electrical insulating materials, laminates, coatings, inks, paints, sealants, resists, composite materials, films, underfill materials, anti-reflection materials, light diffusing materials, light reflecting materials, etc. The present invention also provides an optical semiconductor device in which a semiconductor element is sealed with a cured product of the above-mentioned silicone resin composition of the present invention. EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Note that parts indicate parts by mass, and the viscosity of each component indicates the absolute viscosity at 25°C measured with a rotational viscometer described in JIS K 7117-1:1999. The weight average molecular weight is a value measured by gel permeation chromatography using polystyrene as a standard substance by the above-mentioned method.

[0046] The evaluation test methods used in the following Examples and Comparative Examples are as follows. (1) Appearance Each silicone resin composition was cured at 180° C. for 4 hours, and the color, transparency, and the presence or absence of voids of the resulting cured product (1 mm) were visually inspected. (2) Properties The fluidity of each silicone resin composition before curing was confirmed. 50 g of the composition was added to a 100 ml glass bottle, which was then turned on its side and left to stand at 25° C. for 10 minutes. If the resin flowed out during this time, it was determined to be in a liquid state. (3) Viscosity The viscosity of each silicone resin composition at 25° C. before curing was measured according to the method described in JIS K 7117-1:1999. (4) Refractive index The refractive index of each silicone resin composition before curing was measured at 25° C. using an ATAGO digital refractometer RX-9000α in accordance with the method described in JIS K 0062 for light with a wavelength of 589 nm. (5) Hardness (Type D) Each silicone resin composition was cured at 180° C. for 4 hours, and the hardness of the resulting cured product (120 mm×110 mm×1 mm) was measured using a durometer type D hardness tester in accordance with JIS K 6253-3. (6) Breaking stress and bending modulus Each silicone resin composition was cured at 180° C. for 4 hours, and the breaking stress and flexural modulus of the resulting cured product (120 mm×110 mm×1 mm) were measured using an autograph AG-IS manufactured by Shimadzu Corporation in accordance with JIS K 7171:1994. (7) Adhesiveness 0.25 g of each silicone resin composition was placed on a 2 The copper plate has a base area of ​​45 mm 2 and cured at 180°C for 4 hours to prepare an adhesion test piece. The shear adhesive strength of the test piece was measured at 25 and 150°C using a bond tester DAGE-SERIES-4000PXY (manufactured by DAGE). The adhesive strength retention rate was calculated using the following formula. Adhesive strength retention rate (%) = (Adhesive strength at 150°C [MPa]) / (Adhesive strength at 25°C [MPa] [%]) x 100 (8) Heat resistance test Each silicone resin composition was cured at 180° C. for 4 hours, and the resulting cured product (120 mm×110 mm×1 mm) was then left at 150° C. for 100 hours, after which any change in color was visually confirmed. (9) Water vapor permeability measurement The water vapor permeability of the cured product (120 mm x 110 mm x 1 mm) obtained by curing each silicone resin composition at 180°C for 4 hours was measured using a Lyssy L80-5000 (manufactured by Systech Instruments) water vapor permeability meter at 40°C according to JIS Z 0208:1976 using the cup method. 2 The water vapor permeability below 100 / day was measured using the Mocon method in accordance with JIS K 7129B:2019. (10) Sulfidation resistance 1cm 2 The silver-plated plate was sealed with a silicone resin composition to a thickness of 0.6 mm and cured at 180°C for 4 hours to obtain a sample. The sample was placed in a sealed container together with 3g of sulfur powder and left in a thermostatic chamber at 80°C for 50 hours, after which the initial light reflectance of the silver-plated plate at 450 nm was measured using X-rite8200 manufactured by S.D.G. Corporation. The initial reflectance was 90% in all cases. The sulfurization resistance was calculated by the following formula and evaluated according to the following criteria. Sulfuration resistance (%) = ((Reflectance after sulfuration test [%]) / (Initial reflectance [%])) x 100 (Judgment criteria) ○: Sulfidation resistance is 90% or more. △: Sulfidation resistance is 80% or more but less than 90%. ×: Sulfidation resistance is less than 80% (11) Surface tackiness Each silicone resin composition was cured at 180° C. for 4 hours, and the surface of the resulting cured product (120 mm×110 mm×1 mm) was visually inspected for the presence or absence of dust. (12) Glass transition temperature Each silicone resin composition was cured at 180° C. for 4 hours, and the glass transition temperature of the resulting cured product (120 mm×110 mm×1 mm) was measured using a TA Instruments DMA-800.

[0047] [Synthesis Example 1] Synthesis of branched linear organopolysiloxane (A-1) Phenyltrimethoxysilane (KBM-103, Shin-Etsu Chemical Co., Ltd.) 495.7g (2.50mol), tetramethoxysilane (KBM-04, Shin-Etsu Chemical Co., Ltd.) 190.1g (1.25mol), vinylmethyldimethoxysilane (KBM-1012, Shin-Etsu Chemical Co., Ltd.) 145.3g (1.25mol) were mixed, 13.3g of methanesulfonic acid, 123.9g of pure water, and 1000g of xylene were added, and the mixture was stirred at 90°C for 4 hours. Then, 25.0g of a 50wt% aqueous solution of potassium hydroxide was added, and the mixture was further stirred at 130°C for 16 hours. Acetic acid was added to neutralize the solution, and the solution was washed with 10wt% aqueous sodium sulfate. The organic layer was subjected to azeotropic dehydration at 120° C. for 1 hour, filtered through a 0.45 μm filter paper, and then the solvent was removed by distillation under reduced pressure to prepare a branched organopolysiloxane (A-1). The obtained branched organopolysiloxane (A-1) has an average structure (SiO 4 / 2 ) 0.25 (PhSiO 3 / 2 ) 0.50 ((CH 2 =CH—)MeSiO 2 / 2 ) 0.25 Q 0.25 T 0.5 D Vi 0.25 It has Mw=7700, 0.1 mol / 100 g of hydroxyl groups bonded to silicon atoms, and 0.2 mol / 100 g of vinyl groups bonded to silicon atoms. It has 50% phenyl groups bonded to silicon atoms based on the total number of substituents bonded to silicon atoms.

[0048] [Synthesis Example 2] Synthesis of branched linear organopolysiloxane (A-2) 743.6g (3.75mol) of phenyltrimethoxysilane (KBM-103, manufactured by Shin-Etsu Chemical Co., Ltd.) and 145.3g (1.25mol) of vinylmethyldimethoxysilane (KBM-1012, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed, 13.3g of methanesulfonic acid, 123.9g of pure water and 1000g of xylene were added, and the mixture was stirred at 90°C for 4 hours. Then, 25.0g of a 50wt% aqueous solution of potassium hydroxide was added, and the mixture was further stirred at 130°C for 16 hours. Acetic acid was added to neutralize the solution, and the mixture was washed with 10wt% aqueous sodium sulfate. The organic layer was subjected to azeotropic dehydration at 120°C for 1 hour, filtered with 0.45μm filter paper, and the solvent was removed by distillation under reduced pressure to prepare a branched organopolysiloxane (A-2). The obtained branched organopolysiloxane (A-1) had an average structure (PhSiO 3 / 2 ) 0.75 ((CH 2 =CH—)MeSiO 2 / 2 ) 0.25 T 0.75 D Vi 0.25 It has Mw=3400, 0.1 mol / 100 g of hydroxyl groups bonded to silicon atoms, and 0.2 mol / 100 g of vinyl groups bonded to silicon atoms. It has 60% of phenyl groups bonded to silicon atoms based on the total number of substituents bonded to silicon atoms.

[0049] [Synthesis Example 3] Synthesis of branched linear organopolysiloxane (A-3) 743.6g (3.75mol) of phenyltrimethoxysilane (KBM-103, manufactured by Shin-Etsu Chemical Co., Ltd.) and 243.0g (1.25mol) of vinylphenyldimethoxysilane (KBM-1102, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed, 15.0g of methanesulfonic acid, 123.9g of pure water and 1000g of xylene were added, and the mixture was stirred at 90°C for 4 hours. Then, 25.0g of a 50wt% aqueous solution of potassium hydroxide was added, and the mixture was further stirred at 130°C for 16 hours. Acetic acid was added to neutralize the solution, and the mixture was washed with 10wt% aqueous sodium sulfate. The organic layer was subjected to azeotropic dehydration at 120°C for 1 hour, filtered with 0.45μm filter paper, and the solvent was removed by distillation under reduced pressure to prepare a branched organopolysiloxane (A-3). The obtained branched organopolysiloxane (A-3) had an average structure (PhSiO 3 / 2 ) 0.75 ((CH 2 =CH—)PhSiO 2 / 2 ) 0.25 T 0.75 D Vi 0.25 and has Mw=2000. The amount of hydroxyl groups bonded to silicon atoms is 0.1 mol / 100 g, and the amount of vinyl groups bonded to silicon atoms is 0.2 mol / 100 g. The amount of phenyl groups bonded to silicon atoms is 80% of the total number of substituents bonded to silicon atoms.

[0050] [Synthesis Example 4] Synthesis of branched linear organopolysiloxane (A-4) 743.6g (3.75mol) of phenyltrimethoxysilane (KBM-103, manufactured by Shin-Etsu Chemical Co., Ltd.) and 290.2g (1.25mol) of trimethoxy(7-octen-1-yl)silane (KBM-1083, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed, 13.9g of methanesulfonic acid, 123.9g of pure water and 1000g of xylene were added, and the mixture was stirred at 90°C for 4 hours. Then, 25.0g of a 50wt% aqueous solution of potassium hydroxide was added, and the mixture was further stirred at 130°C for 16 hours. Acetic acid was added to neutralize the solution, and the mixture was washed with 10wt% aqueous sodium sulfate. The organic layer was subjected to azeotropic dehydration at 120°C for 1 hour, filtered with 0.45μm filter paper, and the solvent was removed by distillation under reduced pressure to prepare a branched organopolysiloxane (A-4). The obtained branched organopolysiloxane (A-4) had an average structure (PhSiO 3 / 2 ) 0.75 ((CH 2 =CH(CH 2 ) 6 ―)SiO 3 / 2 ) 0.25 T 0.75 T Vi 0.25and has Mw=7000. The amount of hydroxyl groups bonded to silicon atoms is 0.1 mol / 100 g, and the amount of vinyl groups bonded to silicon atoms is 0.2 mol / 100 g. The amount of phenyl groups bonded to silicon atoms is 60% of the total number of substituents bonded to silicon atoms.

[0051] [Synthesis Example 5] Synthesis of branched linear organopolysiloxane (A-5) 743.6g (3.75mol) of phenyltrimethoxysilane (KBM-103, Shin-Etsu Chemical Co., Ltd.) and 185.1g (1.25mol) of vinyltrimethoxysilane (KBM-1003, Shin-Etsu Chemical Co., Ltd.) were mixed, 13.9g of methanesulfonic acid, 123.9g of pure water, and 1000g of xylene were added, and the mixture was stirred at 90°C for 4 hours. Then, 25.0g of a 50wt% aqueous solution of potassium hydroxide was added, and the mixture was further stirred at 130°C for 16 hours. Acetic acid was added to neutralize the solution, and the mixture was washed with 10wt% aqueous sodium sulfate. The organic layer was subjected to azeotropic dehydration at 120°C for 1 hour, filtered with 0.45μm filter paper, and the solvent was removed by distillation under reduced pressure to prepare a branched organopolysiloxane (A-5). The obtained branched organopolysiloxane (A-5) had an average structure (PhSiO 3 / 2 ) 0.75 ((CH 2 =CH—)SiO 3 / 2 ) 0.25 T 0.75 T Vi 0.25 and has Mw=11200. The amount of hydroxyl groups bonded to silicon atoms is 0.1 mol / 100 g, and the amount of vinyl groups bonded to silicon atoms is 0.2 mol / 100 g. The amount of phenyl groups bonded to silicon atoms is 75% of the total number of substituents bonded to silicon atoms.

[0052] The hydrosilyl group-containing organosilicon compounds used in the examples are as follows: (B-1) Formula (4): [ka] Organohydrogensiloxane represented by the formula (having a hydrogen atom amount bonded to silicon atoms of 0.6 mol / 100 g and being liquid at room temperature (25°C)) (B-2) The following formula (5): [ka] Organosylphenylene compound represented by the formula (the amount of hydrogen atoms bonded to silicon atoms is 1.04 mol / 100 g)

[0053] [Example 1] A silicone resin composition was prepared by adding 100 parts of the branched organopolysiloxane (A-1) obtained in Synthesis Example 1 as component (A), organohydrogensiloxane (B-1) represented by formula (4) above as component (B) in an amount such that the ratio (SiH / SiVi) of the total number of silicon-bonded hydrogen atoms in component (B) to the total number of vinyl groups in component (A) was 1.2, and 0.1 parts of an octyl alcohol-modified solution of chloroplatinic acid (platinum element content: 1% by mass) as component (C) and stirring thoroughly. This composition was heated and molded at 180° C. for 4 hours to form a cured product (120 mm×110 mm×1 mm), and the above-mentioned physical properties were measured. The results are shown in Tables 1-1 and 1-2.

[0054] [Example 2] A silicone resin composition was obtained by repeating the procedure of Example 1, except that, as the component (A), 100 parts of the branched organopolysiloxane (A-2) obtained in Synthesis Example 2 was used in place of the branched organopolysiloxane (A-1) used in Example 1. This composition was heated and molded at 180° C. for 4 hours to form a cured product (120 mm×110 mm×1 mm), and the above-mentioned physical properties were measured. The results are shown in Tables 1-1 and 1-2.

[0055] [Example 3] A silicone resin composition was obtained by repeating the procedure of Example 1, except that, as the component (A), 100 parts of the branched organopolysiloxane (A-3) obtained in Synthesis Example 3 was used instead of the branched organopolysiloxane (A-1) used in Example 1. This composition was heated and molded at 180° C. for 4 hours to form a cured product (120 mm×110 mm×1 mm), and the above-mentioned physical properties were measured. The results are shown in Tables 1-1 and 1-2.

[0056] [Example 4] A silicone resin composition was obtained by repeating the procedure of Example 1, except that, as the component (A), 100 parts of the branched organopolysiloxane (A-4) obtained in Synthesis Example 4 was used in place of the branched organopolysiloxane (A-1) used in Example 1. This composition was heated and molded at 180° C. for 4 hours to form a cured product (120 mm×110 mm×1 mm), and the above-mentioned physical properties were measured. The results are shown in Tables 1-1 and 1-2.

[0057] [Example 5] A silicone resin composition was prepared by adding 100 parts of the branched organopolysiloxane (A-5) obtained in Synthesis Example 5 as component (A), organohydrogensiloxane (B-1) represented by formula (4) above as component (B) in an amount such that the ratio (SiH / SiVi) of the total number of silicon-bonded hydrogen atoms in component (B) to the total number of vinyl groups in component (A) was 1.2, 0.1 parts of an octyl alcohol-modified solution of chloroplatinic acid (platinum element content: 1% by mass) as component (C), and 8 parts of cyclopentanone as component (D) and stirring thoroughly. This composition was heated and molded at 180° C. for 4 hours to form a cured product (120 mm×110 mm×1 mm), and the above-mentioned physical properties were measured. The results are shown in Tables 1-1 and 1-2.

[0058] [Examples 6 to 9] In Examples 1 to 4, the hydrosilyl compound (B-1) was changed to the organosylphenylene compound (B-2) represented by the above formula (5), and the (B-2) component was blended in an amount such that the SiH / SiVi ratio was 1.2. Except for this, the procedures of Examples 1 to 4 were repeated to obtain a cured silicone resin composition. This composition was heated and molded at 180° C. for 4 hours to form a cured product (120 mm×110 mm×1 mm), and the above-mentioned physical properties were measured. The results are shown in Tables 1-1 and 1-2.

[0059] [Example 10] A silicone resin composition was prepared by adding 100 parts of the branched organopolysiloxane (A-5) obtained in Synthesis Example 5 as component (A), organosylphenylene compound (B-2) represented by formula (5) above as component (B) in an amount such that the ratio (SiH / SiVi) of the total number of silicon-bonded hydrogen atoms in component (B) to the total number of vinyl groups in component (A) was 1.2, 0.1 parts of an octyl alcohol-modified solution of chloroplatinic acid (platinum element content: 1 mass %) as component (C), and 15 parts of cyclopentanone as component (D) and stirring thoroughly. This composition was heated and molded at 180° C. for 4 hours to form a cured product (120 mm×110 mm×1 mm), and the above-mentioned physical properties were measured. The results are shown in Tables 1-1 and 1-2.

[0060] [Comparative Synthesis Example 1] 743.7g (3.75mol) of phenyltrimethoxysilane (KBM-103, Shin-Etsu Chemical Co., Ltd.) and 116.3g (0.65mol) of divinyltetramethyldisiloxane (Shin-Etsu Chemical Co., Ltd.) were mixed, 13.0g of methanesulfonic acid, 107.0g of pure water, and 1000g of xylene were added, and the mixture was stirred at 90°C for 4 hours. Then, 25.0g of a 50wt% aqueous solution of potassium hydroxide was added, and the mixture was further stirred at 130°C for 16 hours. Acetic acid was added to neutralize the solution, and the mixture was washed with 10wt% aqueous sodium sulfate. The organic layer was azeotropically dehydrated at 120°C for 1 hour, filtered with a 0.45μm filter paper, and the solvent was removed by distillation under reduced pressure to prepare a branched organopolysiloxane (A-6). The obtained branched organopolysiloxane (A-6) had an average structure (PhSiO 3 / 2 ) 0.75 ((CH 2 =CH―)Me 2 SiO 1 / 2 ) 0.25 T 0.75 M Vi0.25 and has Mw=1400. The amount of hydroxyl groups bonded to silicon atoms is 0.1 mol / 100 g, and the amount of vinyl groups bonded to silicon atoms is 0.2 mol / 100 g. The amount of phenyl groups bonded to silicon atoms is 50% of the total number of substituents bonded to silicon atoms.

[0061] [Comparative Synthesis Example 2] 743.7g (3.75mol) of phenyltrimethoxysilane (KBM-103, Shin-Etsu Chemical Co., Ltd.) and 193.9g (0.65mol) of divinyldimethyldiphenyldisiloxane (Shin-Etsu Chemical Co., Ltd.) were mixed, 14.1g of methanesulfonic acid, 107.0g of pure water, and 1000g of xylene were added, and the mixture was stirred at 90°C for 4 hours. Then, 25.0g of a 50wt% aqueous solution of potassium hydroxide was added, and the mixture was further stirred at 130°C for 16 hours. Acetic acid was added to neutralize the solution, and the mixture was washed with 10wt% aqueous sodium sulfate. The organic layer was azeotropically dehydrated at 120°C for 1 hour, filtered with a 0.45μm filter paper, and the solvent was removed by distillation under reduced pressure to prepare a branched organopolysiloxane (A-7). The obtained branched organopolysiloxane (A-7) had an average structure (PhSiO 3 / 2 ) 0.75 ((CH 2 =CH—)PhMeSiO 1 / 2 ) 0.25 T 0.75 M Vi 0.25 and has Mw=1400. The amount of hydroxyl groups bonded to silicon atoms is 0.1 mol / 100 g, and the amount of vinyl groups bonded to silicon atoms is 0.2 mol / 100 g. The amount of phenyl groups bonded to silicon atoms is 60% of the total number of substituents bonded to silicon atoms.

[0062] [Comparative Example 1] A silicone resin composition was obtained by repeating the procedure of Example 1, except that the branched organopolysiloxane (A-1) of Example 1 was replaced with the branched organopolysiloxane (A-6) obtained in Comparative Synthesis Example 1. This composition was molded by heating at 180°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the above-mentioned physical properties were measured. The results are shown in Table 2.

[0063] [Comparative Example 2] A silicone resin composition was obtained by repeating the procedure of Example 1, except that the branched organopolysiloxane (A-1) of Example 1 was replaced with the branched organopolysiloxane (A-7) obtained in Comparative Synthesis Example 2. This composition was molded by heating at 180°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the above-mentioned physical properties were measured. The results are shown in Table 2.

[0064] [Comparative Example 3] As the component (A), instead of the branched organopolysiloxane (A-1) used in Example 1, [ka] (wherein m=9 and n=19) A silicone resin composition was obtained by repeating the procedure of Example 1, except that a linear organopolysiloxane (A-8) represented by the following formula was used. This composition was molded by heating at 180°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the above-mentioned physical properties were measured. The results are shown in Table 2.

[0065] [Comparative Example 4] A silicone resin composition was obtained by repeating the procedure of Example 6, except that the branched organopolysiloxane (A-1) of Example 6 was replaced with the branched organopolysiloxane (A-6) obtained in Comparative Synthesis Example 1 as component (A). This composition was molded by heating at 180°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the above-mentioned physical properties were measured. The results are shown in Table 2.

[0066] [Comparative Example 5] A silicone resin composition was obtained by repeating the procedure of Example 7, except that the branched organopolysiloxane (A-2) used in Example 7 was replaced with the branched organopolysiloxane (A-7) obtained in Comparative Synthesis Example 2 as the component (A). This composition was molded by heating at 180°C for 4 hours to form a cured product (120mm x 110mm x 1mm), and the above-mentioned physical properties were measured. The results are shown in Table 2.

[0067] The compositions and physical property evaluation results of the silicone resin compositions and their cured products obtained in the above Examples and Comparative Examples are shown in Tables 1-1 and 1-2, and Table 2 below.

[0068] [Table 1-1]

[0069] [Table 1-2]

[0070] [Table 2]

[0071] As shown in Table 2, the silicone resin compositions of Comparative Examples 1, 2, 4, and 5, which contained a branched-chain organopolysiloxane having an alkenyl group in the M unit and no alkenyl-group-containing T unit or D unit, gave cured products with poor adhesion and sulfurization resistance. The cured product of the silicone resin composition of Comparative Example 3, which contained a linear alkenyl-group-containing organopolysiloxane, gave cured products with poor hardness, adhesion, and sulfurization resistance. On the other hand, the silicone resin compositions of Examples 1 to 10 in which the branched-chain organopolysiloxane contained alkenyl group-containing T units or D units gave cured products with sufficient viscosity, appearance, refractive index, hardness, adhesive strength, and sulfurization resistance, as shown in Table 1. This is because the cured products obtained from the branched-chain organopolysiloxane had a rigid structure and maintained a high elastic modulus even at high temperatures. [Industrial Applicability]

[0072] The silicone resin composition of the present invention can give cured products having excellent gas permeation resistance and suitable for use as lens materials for light-emitting semiconductor devices, protective coating agents, molding agents, and the like.

[0073] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. (A) a branched-chain organopolysiloxane represented by the following average formula, which has 10% or more aryl groups bonded to silicon atoms relative to the total number of substituents bonded to silicon atoms and has at least two silicon-bonded alkenyl groups per molecule: (SiO 4/2 ) a (R 1 SiO 3/2 ) b (R 2 SiO 3/2 ) c (R 2 R 3 SiO 2/2 ) d (1) (In the above formula, R 1 are each independently a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyl group other than an alkenyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms; R 2 are each independently an alkenyl group having 2 to 10 carbon atoms; R 3 are each independently a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyl group other than an alkenyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms, and a, b, c, and d are numbers that satisfy a ≧ 0, b > 0, c ≧ 0, and d ≧ 0, with the proviso that c + d > 0 and a + b + c + d = 1. (B) a hydrosilyl group-containing organosilicon compound having two or more SiH groups per molecule, in an amount such that the ratio of the number of hydrosilyl groups in component (B) to the number of alkenyl groups in component (A) is 0.1 to 4.0, and (C) Platinum group metal catalyst catalyst amount 1. A silicone resin composition comprising:

2. 2. The silicone resin composition according to claim 1, wherein, in formula (1), a is a number from 0 to 0.6, b is a number from 0.1 to 0.9, c is a number from 0 to 0.5, d is a number from 0 to 0.5, c+d>0, and a+b+c+d=1 is satisfied.

3. 2. The silicone resin composition according to claim 1, wherein said component (B) is an organosilicon compound selected from organohydrogen(poly)siloxanes, organo(poly)silphenylenes, and organo(poly)silphenylenesiloxanes, having 2 to 200 silicon atoms per molecule and having one or more silicon-bonded aryl groups per molecule.

4. 2. The silicone resin composition according to claim 1, wherein the component (A) has a weight average molecular weight of 1,000 to 50,000 as determined by gel permeation chromatography using polystyrene as the standard substance.

5. A cured product of the silicone resin composition according to any one of claims 1 to 4.

6. 6. The cured product according to claim 5, which has a type D hardness in the range of 30 to 90 as measured by the method described in JIS K 6253-3.

7. 6. The cured product according to claim 5, wherein the cured product has a refractive index at a wavelength of 589 nm measured by the method described in JIS K 0062 in the range of 1.45 to 1.

60.

8. An optical semiconductor device comprising the cured product according to any one of claims 5 to 7 and an optical semiconductor element.

Citation Information

Patent Citations

  • Curable silicone resin composition

    JP2004339482A

  • Polymer obtained by using silsesquioxane derivative

    JP2006070049A

  • Silicone resin composition for light-emitting diode element, and light-emitting diode element

    JP2010109034A

  • Silicone resin composition, luminous substance-containing wavelength-converting film, and cured product thereof

    JP2013144757A

  • Silicone resin composition, silicone laminated substrate using the same, method for producing the silicone laminated substrate, and LED device

    JP2014088459A